The carbon cycle response to two El Nino types: an observational study. (23rd January 2018) - Chylek, Petr; Tans, Pieter; Christy, John; Dubey, Manvendra K
Abstract: We analyze monthly tropical near surface air temperature and Mauna Loa Observatory carbon dioxide (CO2 ) data within 1960–2016 to identify different carbon cycle responses for two El Nino types: El Ninos originating in the central tropical Pacific (CP El Nino) and El Ninos originating in the eastern tropical Pacific (EP El Nino). We find significant differences between the two types of El Nino events with respect to time delay of the CO2 rise rate that follows the increase in tropical near surface air temperatures caused by El Nino events. The average time lag of the CP El Nino is 4.0 ± 1.7 months, while the mean time lag of EP El Nino is found to be 8.5 ± 2.3 months. The average lag of all considered 1960–2016 El Ninos is 5.2 ± 2.7 months. In contrast the sensitivity of the CO2 growth rate to tropical near surface air temperature increase is determined to be about the same for both El Nino types equal to 2.8 ± 0.9 ppm yr −1 K −1 (or 5.9 ± 1.9 GtC yr −1 K −1 ). Our results should be useful for the understanding of the carbon cycle and constraining it in climate models.